Mesenchymal Stromal Cell Secretome: Immunomodulation, Tissue Repair and Effects on Neurodegenerative Conditions - Zriek, Fatima; Di Battista, John A.; Alaaeddine, Nada (Current Stem Cell Research & Therapy, 2021)
Mesenchymal stromal cells (MSCs) have emerged as a modern development in therapeutics for a wide variety of diseases. Secreted paracrine factors constitute the principal components harboring the restorative promise of MSCs. Recent studies demonstrate that MSC-derived secretomes are composed of several molecules targeting a variety of biological processes that impact tissue repair, growth and immunomodulation. Indeed, secretomes interact with immune cells, activating regulatory anti-inflammatory phenotypes. In this review, we discuss the action of MSC-derived secretomes in promoting tissue regeneration, opposing the inflammatory response in context-specific cases, and treating neurodegenerative diseases, resulting from chronic neuroinflammation.
Keywords: regeneration